Communities and Technologies 2005 2005
DOI: 10.1007/1-4020-3591-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Design for Informal Learning in Community Computing

Abstract: Abstract. We discuss the role and characteristics of informal learning in a community computing context. We argue that minimalist design can be adapted to the needs of community computing, and that its principles can be used to envision and develop community activities and technologies that promote active learning. We illustrate these ideas with several community computing projects that exemplify how to embed learning in meaningful activities, enable learners to make progress quickly, promote thinking and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These different needs and expectations could be shaped by the objectives of the activity (e.g., competitive vs. recreational running), demographic characteristics, or familiarity with applications, which need to be further examined in the next phases of study. Previous research has shown that supporting selection and easy customization of the functions and features of an application could reduce the complexity of the application as well as enhance user satisfaction (Rosson & Carroll, 2005). In addition, the next phases of the study, which involves a survey and experiment, will examine college students' value structure of how to choose and utilize mobile wellness applications.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…These different needs and expectations could be shaped by the objectives of the activity (e.g., competitive vs. recreational running), demographic characteristics, or familiarity with applications, which need to be further examined in the next phases of study. Previous research has shown that supporting selection and easy customization of the functions and features of an application could reduce the complexity of the application as well as enhance user satisfaction (Rosson & Carroll, 2005). In addition, the next phases of the study, which involves a survey and experiment, will examine college students' value structure of how to choose and utilize mobile wellness applications.…”
Section: Discussion and Future Researchmentioning
confidence: 99%